City-Regions : new geographies of uneven development and inequality - Etherington, David
Etherington D. and Jones M. City-regions: new geographies of uneven development and inequality, Regional Studies. Recent years have witnessed a burgeoning literature on the ‘new regionalism’. Protagonists have made persuasive arguments about regions as successful models of economic and social development. This paper argues that the championing of ‘city-regions’ provides an opportunity for taking these debates further. It draws on research taking place on the Sheffield City-Region, UK, and particularly discusses the interrelationships between competitiveness, work–welfare regimes – those policies and strategies dealing with labour market governance and welfare state restructuring – labour market inequalities and low pay. The paper suggests that city-regions reinforce, and have the potential to increase, rather than resolve, uneven development and socio-spatial inequalities.